2014
DOI: 10.2134/jeq2013.10.0424
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of Tillage Practices and Phosphorus Fertilization on Soil Phosphorus Forms as Determined by 31 P Nuclear Magnetic Resonance Spectroscopy

Abstract: Conservation tillage practices have become increasingly common in recent years to reduce soil erosion, improve water conservation, and increase soil organic matter. Research suggests that conservation tillage can stratify soil test phosphorus (P), but little is known about the effects on soil organic P. This study was conducted to assess the long-term effects of tillage practices (no-till [NT] and mouldboard plowing) and P fertilization (0 and 35 kg P ha) on the distribution of P species in the soil profile. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 62 publications
5
62
0
Order By: Relevance
“…Messiga et al (2012) measured greater P M3 under fertilized NT in comparison with MP soils. On the same experimental site, Abdi et al (2014) reported the stratification of P M3 and orthophosphate concentrations under NT management. The transformation of residual P derived from fertilizer into less labile forms might be limited under NT, because broadcast P fertilizer interacts with plant residues, blocking sorption sites, and therefore, adsorption or fixation on the solid phase (Messiga et al 2012).…”
Section: Nongrowing Season Soil Phosphate As Measured With Anionic Exmentioning
confidence: 94%
See 2 more Smart Citations
“…Messiga et al (2012) measured greater P M3 under fertilized NT in comparison with MP soils. On the same experimental site, Abdi et al (2014) reported the stratification of P M3 and orthophosphate concentrations under NT management. The transformation of residual P derived from fertilizer into less labile forms might be limited under NT, because broadcast P fertilizer interacts with plant residues, blocking sorption sites, and therefore, adsorption or fixation on the solid phase (Messiga et al 2012).…”
Section: Nongrowing Season Soil Phosphate As Measured With Anionic Exmentioning
confidence: 94%
“…The transformation of residual P derived from fertilizer into less labile forms might be limited under NT, because broadcast P fertilizer interacts with plant residues, blocking sorption sites, and therefore, adsorption or fixation on the solid phase (Messiga et al 2012). In addition, the limited transfer of residual P from the enriched upper layer to depleted lower layers due to the low mobility of P also contributed to the differences in soil test P between the P 0 treatment and the P-fertilized plots (Messiga et al 2012;Abdi et al 2014). …”
Section: Nongrowing Season Soil Phosphate As Measured With Anionic Exmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review on P distribution in the soil profile of fertilized NT cropland shows greater soil test P concentrations in the top 5-cm layer and, to some extent, down to the 10-cm depth, as well as a marked depletion of P in subsequent sublayers (Abdi et al, 2014;Cade-Menun et al, 2010). Messiga et al (2012) observed low soil test P concentration in the 10-to 20-cm layer of fertilized NT plots in comparison with MP plots, indicating that under NT, P was depleted in this layer.…”
mentioning
confidence: 99%
“…Numerous studies also showed P stratification in soil under different tillage systems where ZT system associated with higher concentration of P due to preferential movement of P in the soil (Abdi et al, 2014). Moreover, the shallower incorporation of crop residues and fertilizer P as well as small P losses due to water erosion under CA leads to higher P contents in the surface soil.…”
Section: Nutrient Dynamicsmentioning
confidence: 99%